PENGARUH SISA LEBIH PERHITUNGAN ANGGARAN (SiLPA) DAN FINANCIAL DISTRESS TERHADAP MANIPULASI AKRUAL PADA PEMERINTAH DAERAH DI INDONESIA - Shafira, Cut Alya; Abdullah, Syukriy (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to examine the effect of Calculation of Budget Excess (SiLPA) and Financial Distress on Accrual Manipulation in Indonesian Regional Governments. The object of this research is all district/city governments in Indonesia. The selection of the object of this research is based on the number of cases in local governments in districts and cities that cause problems. Researchers cannot see problems from one district or one city because this research is to see as a whole whether all local governments experience accrual manipulation, so this study takes the object of all local governments in Indonesia. The data used is secondary data from the audited district/city financial statements. The sample in this study amounted to 438 districts/cities for the 2019 fiscal year. Multiple linear regression models were used to test the hypothesis. The results showed that the two independent variables, namely SiLPA and Financial Distress had a positive effect on Accrual Manipulation.